Intramuscular Aripiprazole in the Acute Management of Psychomotor Agitation. Issue 6 (15th March 2013) - De, Sergio; Cuomo, Ilaria; Lionetto, Luana; Janiri, Delfina; Simmaco, Maurizio; Caloro, Matteo; De, Simone; Piazzi, Gioia; Simonetti, Alessio; Telesforo, C Ludovica; Sciarretta, Antonio; Caccia, Federica; et al.
<x xml:space="preserve">Abstract</x> Study Objective To assess acute efficacy and safety of 9.75 mg of intramuscular (IM) injections of the atypical antipsychiatric aripiprazole in patients with schizophrenia or bipolar disorder and acute agitation. Design Open‐label trial of IM injections of aripiprazole and 24‐hour monitoring of clinical response in patients with major psychoses and acute agitation. Partial analysis of blood levels of the administered drug to correlate with clinical response. Setting Acute psychiatric care wards in a single university hospital. Patients A total of 201 acutely agitated patients (79 with schizophrenia and 122 with bipolar disorder I). Intervention Aripiprazole 9.75 mg IM injection. Measurements and Main Results We evaluated clinical response using the Excitatory Component of the Positive and Negative Syndrome Scale (PANSS‐EC), the Agitation/Calmness Evaluation Scale (ACES), and the Clinical Global Impressions scale (CGI). Assessments were conducted 30, 60, 90, and 120 minutes and 24 hours after the first injection for PANSS‐EC and ACES, and 2, 4, 6, and 24 hours for CGI. Response was at least a 40% decrease in PANSS‐EC scores. We measured serum aripiprazole and dehydroaripiprazole levels in a subsample. IM aripiprazole significantly improved clinical measures. PANSS‐EC improved progressively, starting after 30 minutes. ACES improved after 90 minutes and continued thereafter. Effects were sustained, with steadily decreasing CGI scores, until the 24th hour. Response rate was 83.6% after 2 hours, but with repeat injections, it rose to over 90% with no differences among diagnostic groups. Although there were gender differences in the response to individual PANSS‐EC items, the responses were similar overall. Neither clinical monitoring nor patient reporting revealed any side effects. No therapeutic window was identified, and levels did not correlate with any clinical measure. Conclusion Aripiprazole was effective and safe in reducing acute agitation in patients with bipolar disorder or schizophrenia. Our results compare favorably to double‐blind trials, probably due to higher expectations in trials involving no placebo arm. Absence of side effects could be related to the short observation time.